Making the Invisible Visible: Paradoxical Effects of Intersectional Invisibility on the Career Experiences of Executive Black Women - Smith, Alexis Nicole; Watkins, Marla Baskerville; Ladge, Jamie J.; Carlton, Pamela (Academy of Management Journal, 2019)
The unique and complex experiences of and challenges for Black women, which are tied to their intersecting marginalized identities, have largely been overlooked in management research. Although Black women are physically visible in that they are different from most of their colleagues, intersectional invisibility research suggests that they can be simultaneously invisible—easily overlooked or disregarded—because they are non-prototypical members of their gender and racial identity groups. To shed new light on the role that intersectional invisibility plays in Black women’s perceptions and experiences, we conducted two waves of in-depth interviews across seven years with 59 Black women who occupy senior-level positions in organizations. We develop a theoretical model to explain the paradoxical effects of executive Black women’s “outsider within” status in which they simultaneously experience opportunities and constraints associated with two forms of intersectional invisibility: benign and hostile. To manage both forms of intersectional invisibility, executive Black Women adopt a number of critical strategies to gain credible visibility needed to ascend in their careers.